2015
DOI: 10.1111/tct.12296
|View full text |Cite
|
Sign up to set email alerts
|

Peer-assisted bedside teaching rounds

Abstract: Our findings demonstrate that peer-directed learning in undergraduate medical education can be effectively implemented in the clinical arena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Backes, Reber, Trittmann, Huang, Tobmlin, Moorehead, Bauer, Smith and Mahan (2011) found that 87.5% of residents in their study believed fellows to be important in their learning experiences. Another study with medical student participants revealed that peers viewed the senior medical students as "clinical teachers" (Doumouras, Rush, Campbell & Taylor, 2015). This can be translated into the small groups during Grand Rounds by utilizing the third-year students as mentors or clinical teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Backes, Reber, Trittmann, Huang, Tobmlin, Moorehead, Bauer, Smith and Mahan (2011) found that 87.5% of residents in their study believed fellows to be important in their learning experiences. Another study with medical student participants revealed that peers viewed the senior medical students as "clinical teachers" (Doumouras, Rush, Campbell & Taylor, 2015). This can be translated into the small groups during Grand Rounds by utilizing the third-year students as mentors or clinical teachers.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Students readily learn from one another and from the preparation of educational material. 7,8 It has been suggested that peer interaction is necessary for optimal learning, in that students who learn in groups significantly outperform those that process information individually. 9 Peer-to-peer learning also engages medical students in their lifelong role as physician-teachers.…”
Section: 2mentioning
confidence: 99%
“…9 Peer-to-peer learning also engages medical students in their lifelong role as physician-teachers. 7 In recent years, studies have shown the efficacy of students as bedside teachers, 7,10 simulated patients, 11 OSCE examiners, 12,13 and even OSCE designers. 14 For example, in a study by Haist et al, first-year medical students randomized to physical examination sessions taught by fourth-year students performed equally well as those taught by faculty in objective measures.…”
Section: 2mentioning
confidence: 99%
“…From Canada, Doumouras et al . describe a model in which senior medical students teach junior students in clinical settings – at the bedside . Again both groups benefited from the experience: the juniors gained confidence and comfort with patients, whereas the seniors learned from preparing for and delivering the teaching.…”
Section: Peers and Patients As Educatorsmentioning
confidence: 99%
“…describe a model in which senior medical students teach junior students in clinical settings -at the bedside. 5 Again both groups benefi ted from the experience: the juniors gained confi dence and comfort with patients, whereas the seniors learned from preparing for and delivering the teaching. Finally, Burgess and Mellis of Australia investigate how medical students perceive the experience of being formatively assessed by, and receiving feedback from, their peers.…”
Section: Peers and Patients As Educatorsmentioning
confidence: 99%